ELECTRONIC CUSTOMS AS THE MAIN VECTOR OF CUSTOMS AUTHORITIES DEVELOPMENT IN THE CONTEXT OF DIGITALIZATION OF THE RUSSIAN ECONOMY - A. V. Sal’nikova; M. A. Chernova (Вестник университета)
The essence, purpose and concept of electronic customs have been considered. According to the results of the analysis of regulatory legal acts and scientific literature, a conclusion about the absence of a system concept of electronic customs has been drawn. Based on the identified key characteristics, the corresponding author’s definition has been formulated. The problems of the development of the electronic customs institute in the Russian Federation have been analysed, the main ones are the imperfection of the technologies used, the insufficient qualifications of electronic customs personnel, the imperfect mechanism of interaction between electronic customs and other elements of the system, the absence of criteria for the effectiveness of electronic customs, the theoretical foundation and the conceptual framework of the electronic customs institute. The prospects for the development of electronic customs have been determined and conclusions about the need to improve the theoretical, legislative and technical basis for the development of customs authorities in the context of the digitalization of the economy of the Russian Federation have been made.